Taming Giants: How Ordoliberal Competition Theory Can Address Power in the Digital Age - Anselm Küsters; Isabel Oakes (Journal of Contextual Economics – Schmollers Jahrbuch, 2021)
In comparing the historical circumstances in which ordoliberalism emerged with the socio-economic and political trends of today, this study identifies parallels that can provide useful insights into tackling current challenges in the digital age. On this basis, the study explores whether ordoliberal concepts like "complete competition," "interdependence of orders," and Vitalpolitik, and the lessons from the past that they incorporate, can help reform European competition law for the digital economy. Along with a renewed focus on structural remedies, per se rules and a historical interpretation of European competition norms, ordoliberal theory could contribute to a reformed approach to competition policy that can tame the power of today's digital giants more effectively.
Keywords: B25; B41; D40; K21; L40; 330; Ordoliberalism; Competition Law; Digitalization; GAFAM